Prevalence of chronic periodontitis in an obese population: A preliminary study - Khan, S.; Saub, R.; Vaithilingam, R.D.; Safii, S.H.; Vethakkan, S.R.; Baharuddin, N.A. (BioMed Central, 2015)
Background: Chronic periodontitis (CP) is a global public health issue. Studies have suggested CP could be linked to obesity due to their similar pathophysiological pathway. The aim of this study is to determine the prevalence of CP and to assess the predictors for CP among the obese Malaysian population.